Dimmer and neon transformer as a power controllable generator for atmospheric pressure plasma jet - Rosnah Mohd Zin; Chin Fhong Soon; Nadhia Mohd Yusof; Elfa Rizan Rizon; Kian Sek Tee; Mohd Khairul Ahmad; Nafarizal Nayan (Institute of Advanced Engineering and Science, 2019)
The feasibility of a dimmer and neon transformer to provide power control to the atmospheric pressure plasma jet (APPJ) is presented in this paper. The standard neon transformer was previously shown applicable to power up a plasma torch to generate plasma irradiation of an APPJ at 8.64kv and 35kHz. However, the plasma emission is not controllable. In this study, a lamp dimmer was proposed to function as a power controller to the neon transformer which drives the generation of plasma and discharged with argon gas. With the dimmer output voltage adjustable from 60 - 220V, the power and current of the dimmer were variable from 8.4 to 83.6 W and 0.08 and 0.38 A, respectively. The temperature measured at the quartz tube and sample exposure site were less than 50oC suggested that the APPJ produced were non-thermal. A simple test by exposing plasma plume to a leaf sample showed that the plasma produced were non-damaging to the leaf. This portable system can provide control to the APPJ and applicable for bioengineering studies.